Theranostic Options for Radioiodine-Refractory Differentiated Thyroid Carcinoma: Recent Advances, Challenges, and Road Ahead - Satapathy, Swayamjeet; Bal, Chandrasekhar (Frontiers in Endocrinology, 2022)
Radioiodine-refractory differentiated thyroid cancer (RAIR-DTC), though uncommon, presents a considerable therapeutic challenge with poor long-term outcomes. Currently, tyrosine kinase inhibitors are the mainstay of treatment for advanced RAIR-DTC patients. However, these agents are associated with a multitude of adverse events with resultant deterioration in the quality-of-life of the patients. Targeted theranostic approaches with radiolabelled integrin binders and fibroblast activation protein- (FAP)-inhibitors seem to have a promising role in the management of such patients. This mini-review focuses on these novel theranostic strategies in RAIR-DTC, with emphasis on recent advances, existing challenges, and future directions.